Hubungan Pengetahuan Ibu Dan Pola Asuh Terhadap Kejeadian Underweight Pada Balita Usia 12-59 Bulan Di Desa Tallu Banua - Nisa Andriani; Diesna Sari; Nurpatwa Wilda Ningsi; Rasmawati (Universitas Sulawesi Barat, 2024)
Backround : Underweight is a condition where infants and toddlers are unable to reach their ideal weight. UNICEF in 2020 estimated that 45.4 million children were underweight, while according to SKI 2023, the prevalence of underweight toddlers in West Sulawesi was 23.1% and in Majene district was 23.8%. Objective : This study aims to determine the relationship between maternal knowledge and parenting patterns on the incidence of underweight in toddlers aged 12-59 months in Tallu Banua Village. Method : This study uses a cross-sectional approach, with purposive sampling technique, and a sample size of 94 respondents. Data collection using questionnaires and secondary data sources. Data were analyzed using the chi-square test with a significance value of < 0.05. Result : The research results show that maternal knowledge is mostly in the insufficient category with underweight incidence, with a p-value of 0.000 (p<0.05), while parenting patterns with underweight incidence in Tallu Banua Village have a p-value of 0.448 (p>0.05). Conclusion : The conclusion of this study indicates that there is a significant relationship between maternal knowledge and underweight incidence in children aged 12-59 months in Tallu Banua Village, and there is no significant relationship between maternal parenting patterns and underweight incidence in children aged 12-59 months in Tallu Banua Village.